Application of Knowledge Management as Strengthening the Maritime Sector in Indonesian SOEs - Rizki HAMDANI; Muhammad Shareza HAFIZ; Arif Pratama MARPAUNG; Wulan DARI; Ilham Akbar DARMAWAN; Hartato RIANTO (Communications of International Proceedings, 2021)
The purpose of this study is to analyze the implementation of knowledge management that has been successfully carried out by State-Owned Enterprises (SOE), especially PT Pertamina with the KOMET (Pertamina Knowledge Management) program so that this success can be applied to SOE companies in the maritime sector. This research is conducted by a qualitative descriptive with the single case study, data collection was carried out to obtain secondary data with research instruments using observation and documentation from electronic printed media, journals, and official websites of state-owned companies. This study determines that the application of knowledge management has managerial implications in overcoming barriers and increasing knowledge by building long-term employee loyalty and strong corporate culture and also enabling cross-business divisions to share knowledge, so this application is very good for SOE companies, especially in the maritime sector in dealing with free trade market.
Keywords: Maritime; SOE; Knowledge Management; Free Trade.